ANALISIS DAYA SAING EKSPO KOPI INDONESIA, BRAZIL, KOLOMBIA, DAN VIETNAM - Burhani Maulana Suprayogi; Zainul Arifin; M. Kholid Mawardi (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
Coffee competitiveness as measured by comparative competitiveness, export position of Indonesian coffee, Brazil, Colombia, and Vietnam, and the competitive advantage of Indonesian coffee industry. The type of research used is descriptive with two approaches that is quantitative and qualitative. Then with a quantitative approach, the research used is the analysis tool RCA Index (Revealed Comparative Advantage) and ISP (Index of Trade Specialization). While the analysis using the Diamond Porter theory for a qualitative approach. This study uses primary and secondary data and use time series data types from 1996 to 2014. Based on RCA and ISP analysis, Indonesia has a comparative advantage and tends to be a coffee exporter country. However, Indonesia has the lowest competitiveness compared to Brazil, Colombia, and Vietnam. Based on Diamond Porter's theory analysis, Indonesia is weak on production factors and Government factors. Keywords: Comparative Advantage, Competitive Advantage, Competitiveness, Coffee Export. ABSTRAK Daya saing kopi yang diukur melalui tingkat daya saing komparatif, posisi ekspor kopi Indonesia, Brazil, Kolombia, dan Vietnam, dan keunggulan kompetitif industri kopi Indonesia. Jenis penelitian yang digunakan yaitu deskriptif dengan pendekatan dua jenis yaitu kuantitatif dan kualitatif. Kemudian dengan pendekatan kuantitatif, penelitian yang digunakan yaitu alat analisis Indeks RCA (Revealed Comparative Advantage) dan ISP (Indeks Spesialisasi Perdagangan). Sedangkan analisis menggunakan teori Diamond Porter untuk pendekatan kualitatif. Penelitian ini menggunakan data primer dan sekunder dengan jenis data time series periode tahun 1996 – 2014. Analisis indeks RCA dan ISP Indonesia menunjukkan keunggulan komparatif dan lebih baik sebagai negara eksportir kopi. Namun Indonesia memiliki daya saing terendah dibandingkan dengan Brazil, Kolombia, dan Vietnam. Berdasarkan analisis teori Diamond Porter, Indonesia lemah pada faktor produksi dan faktor Pemerintah. Kata Kunci : Keunggulan komparatif, Keunggulan Kompetitif, Daya Saing, Ekspor Kopi.